Space, Place and Desistance from Drug Use - Ben Hunter; Stephen Farrall (Oñati Socio-Legal Series)
As centres of human existence, places and spaces are vital for individuals’ understanding of themselves and who they might become. We explore these aspects of existence through a longitudinal study of 43 current and former drug users. First, we identify the differences between those who have desisted from drug use and those who continued. These differences manifested themselves in the routines that frequently governed desisters’ lives. Persisters had very little in the way of routines that served to structure their time and where they did these were more likely to be seen as a burden. Further, the places our respondents occupied served as indications of their own understandings of their self and their efforts to desist. Second, we investigate in detail one individual’s desistance from drug use and the accompanying change in his existential geography. As Peter desisted his goals and aspirations changed, becoming less focused on avoiding drug use and directed to more positive desires. We discuss the implications of this work for desistance research.